2000
DOI: 10.1046/j.1439-0272.2000.00358.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term treatment with human pure follicle-stimulating hormone on semen parameters and sperm-cell ultrastructure in idiopathic oligoteratoasthenozoospermia

Abstract: Ten subfertile men affected by idiopathic oligoteratoasthenozoospermia and exhibiting normal serum hormone levels received a long-term treatment with human pure follicle-stimulating hormone (hp-FSH) (150 IU, intramuscularly, three times per week for 6 months). Semen parameters and ultrastructural features of spermatozoa were evaluated before and after therapy. The results showed an increase in sperm cell concentration and, more interestingly, motility. Electron microscopic examination revealed an improved fine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In vitro culture in rhFSH-supplemented medium increased motility of testicular spermatozoa (12). Finally, some more recent studies showed some direct effects on basic sperm parameters with both uFSH (13) and rhFSH (14,15).…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In vitro culture in rhFSH-supplemented medium increased motility of testicular spermatozoa (12). Finally, some more recent studies showed some direct effects on basic sperm parameters with both uFSH (13) and rhFSH (14,15).…”
mentioning
confidence: 86%
“…Therefore, we administered 1,050 IU rhFSH per week, which is more than twice as high as the doses (450 IU FSH/wk) commonly used by most investigators with both uFSH (4,5,10,11,13,24,25) and rhFSH (14,15,26) but similar to those used by Ben Rafael et al (6) with uFSH and by Kamischke et al (7) with rhFSH.…”
mentioning
confidence: 99%
“…The findings of this study demonstrate that, in oligozoospermic patients with male‐factor infertility and normal FSH, LH and T serum levels, a treatment with high doses of rhFSH clearly stimulates spermatogenesis and increases sperm concentration and total sperm number in the ejaculate, reaching the lower limits of the normal range of the WHO criteria. These outcomes largely confirm our previous pilot study (Paradisi et al ., ) and are somehow in line with many other studies (Foresta et al ., , , ; Arnaldi et al ., ; Caroppo et al ., ; Baccetti et al ., ), which used mainly lower doses of FSH, while disagree with the data of Kamischke et al . (), who used rhFSH doses similar to ours.…”
Section: Discussionmentioning
confidence: 99%
“…Some Authors (Acosta et al ., ; Matorras et al ., ; Kamischke et al ., ; Ben‐Rafael et al ., ) and also some systematic reviews (Kamischke & Nieschlag, ; Kumar et al ., ) denied evidence in support of FSH treatment for enhancing male infertility. On the other hand, more numerous and recent studies (Acosta et al ., ; Bartoov et al ., ; Ashkenazi et al ., ; Arnaldi et al ., ; Foresta et al ., , ; Caroppo et al ., ; Baccetti et al ., ; Paradisi et al ., ) and newer meta‐analyses (Isidori et al ., ; Attia et al ., ) including larger number of studies confuted the previous outcomes, demonstrating a significant FSH action on sperm parameters and pregnancy rate in idiopathic male‐factor infertility.…”
Section: Introductionmentioning
confidence: 99%
“…Although intracytoplasmic sperm injection (ICSI) 1 has revolutionized the empirical treatment of severe male infertility, 2 several studies have demonstrated that sperm structure may impede ICSI outcome. 3,4 Low fertilization rates associated with poor sperm quality seem to be due to acrosomal dysfunction or disturbed axonemal or DNA integrity. 5 Some investigators 3,4 have reported that FSH treatment may restore sperm structure, even though the benefits of FSH therapy on other sperm parameters are still controversial.…”
Section: Hormonal Therapy To Idiopathic Infertile Menmentioning
confidence: 99%